Venezuelan bust, baseball boom : Andrés Reiner and scouting on the new frontier - Jamail, Milton H. (University of Nebraska Press, 2008)
While other teams were looking to the Dominican Republic for new talent, Houston Astros' scout Andrés Reiner saw an untapped niche in Venezuela. Venezuelan Bust, Baseball Boom recounts how, over the next fifteen years, Reiner signed nearly one hundred players, nineteen of whom reached the majors. The stories of these players?among them Bobby Abreu, Johán Santana, Melvin Mora, Carlos Guillén, and Freddy García?are interwoven with Reiner?s own, together creating a fascinating portrait of a curious character in the annals of sports and a richly textured picture of the opening of Venezuela as base.